From Competition to Configuration - Trinanda, Ghea Anissah (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
This article examines the transformation of two types of knowledge—government/official knowledge, which represents